1975
DOI: 10.1037/0278-7393.1.2.126
|View full text |Cite
|
Sign up to set email alerts
|

An application of the mnemonic keyword method to the acquisition of a Russian vocabulary.

Abstract: The experiment reported here evaluated the effectiveness of a mnemonic procedure, the keyword method, for learning a foreign language vocabulary. The method used divides the study of a vocabulary item into two stages. The first stage requires the subject to associate the spoken foreign word with an English word, the keyword, that sounds like some part of the foreign word; the second stage requires him to form a mental image of the keyword interacting with the English translation. Thus, the keyword method can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
141
1
8

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 6 publications
5
141
1
8
Order By: Relevance
“…The results of several studies have indicated that age is an important variable in the use of imagery-based recall methods and that such methods are useful for adult people (Atkinson & Rough, 1975;Shapiro & Waters, 2005); however, the modified keyword method does not always enhance the word recall of adult subjects (Hall, Wilson, & Patterson, 1981;Pressley, 1987;Desrochers, Wieland, & Cote, 1991). In line with that, the keyword method is effective among elementary school children (e.g., Wyra, Lawson, & Hungi, 2007).…”
Section: Empirical Studies On the Effectiveness Of Using Mnemonic-basmentioning
confidence: 51%
“…The results of several studies have indicated that age is an important variable in the use of imagery-based recall methods and that such methods are useful for adult people (Atkinson & Rough, 1975;Shapiro & Waters, 2005); however, the modified keyword method does not always enhance the word recall of adult subjects (Hall, Wilson, & Patterson, 1981;Pressley, 1987;Desrochers, Wieland, & Cote, 1991). In line with that, the keyword method is effective among elementary school children (e.g., Wyra, Lawson, & Hungi, 2007).…”
Section: Empirical Studies On the Effectiveness Of Using Mnemonic-basmentioning
confidence: 51%
“…The research on the mediational role of imagery in associative learning and memory can be traced back to earlier psychological studies (e.g., Bower, 1970;Paivio, 1969). In an imagery mediation study in English-Russian word association, Atkinson and Raugh (1975) found that English-speaking participants learned significantly more meaning-word associations via mental images, with the memory sustaining up to six weeks later. This study suggests that visual imagery may help with long-term memory for information retention.…”
Section: Review Of the Literature Psychological Theories In Visual Immentioning
confidence: 99%
“…One of the most comprehensive examples of the positive effects of experimenter-supplied keyword mnemonics is Atkinson (1975). In this review of his work, he discusses an experiment (Atkinson & Raugh, 1975) in which participants learned 120 Russian-English word pairs over three days with experimenter provided keywords or without. This experiment showed a recall level of 72% in the mnemonics condition the day after the final learning session with only 46% recall in the control condition.…”
Section: Mnemonics (Strategy Use)mentioning
confidence: 99%